Automobile heat insulation film and preparation method thereof
By using sputtering technology to form a modified substrate and applying a modified coating in the automotive thermal insulation film, the problem of insufficient insulation effect and scratch resistance of the existing automotive thermal insulation film is solved, and more efficient heat insulation and better scratch resistance are achieved.
Patent Information
- Application Number
- CN202411859560.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The thermal insulation effect of existing automotive thermal insulation films is limited, and scratches are prone to appear on the surface of the film after long-term use, which affects the beauty and safety.
The substrate is used as a sputtering substrate, zinc oxide, antimony tin oxide and zinc oxide are sputtered successively to form a sputtering layer to produce a modified substrate, and a modified coating is applied to the surface, and an automobile thermal insulation film is formed by curing ultraviolet light.
The insulation effect of the automotive thermal insulation film is improved, and the branched structure and self-repair ability of the modified coating are enhanced, and the service life is extended.
Smart Images

Figure BDA0005192851250000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat insulation film preparation, and in particular to an automobile heat insulation film and a preparation method thereof. Background Art
[0002] With the rapid development of automobile technology and the growing demand of consumers, the comfort and safety of automobiles have become the focus of major automobile manufacturers and improvement suppliers. Especially in the hot summer, the high temperature inside the car is a great challenge to the comfort of riding. At present, there are various automotive insulation film products on the market, which mainly achieve the cooling effect by reflecting heat or absorbing heat and then radiating it. There are some shortcomings in the existing technology, including limited insulation performance and general scratch resistance on the surface of the insulation film. After long-term use, scratches accumulate on the surface, which seriously affects the appearance and even affects driving, endangering the safety of the driver. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an automobile thermal insulation film, which solves the problem that the thermal insulation effect of the thermal insulation film at present is average and scratches will appear on the surface of the film after long-term use.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing an automobile thermal insulation film comprises the following steps:
[0006] A substrate is used as a sputtering substrate, zinc aluminum oxide is used as a first target material, antimony tin oxide is used as a second target material, and zinc aluminum oxide is used as a third target material. Under the conditions of a sputtering power of 80-100 W, an argon gas flow rate of 25-40 sccm, and a sputtering gas pressure of 0.75-1 Pa, sputtering treatment is performed in sequence to form a sputtering layer to obtain a modified substrate. A modified coating is coated on a side of the modified substrate away from the sputtering layer. Under the conditions of a temperature of 30-40° C. and irradiation with 365 nm ultraviolet light, ultraviolet curing is performed for 10-15 minutes to obtain an automotive thermal insulation film.
[0007] Furthermore, the mass ratio of zinc oxide to aluminum oxide in the first target material zinc oxide aluminum is 98:2, and the background vacuum is 6×10 -4 The mass ratio of tin oxide to antimony oxide in the second target material tin antimony oxide is 95:5, and the background vacuum is 5×10 -4 , the third target material is the same as the first target material.
[0008] Further, the base film is made by the following steps:
[0009] Step A1: dispersing lanthanum hexaboride in ethanol, stirring and adding KH550 and deionized water at a speed of 120-150 r / min and a temperature of 40-50° C., and reacting for 3-5 hours to obtain pretreated lanthanum hexaboride; dispersing titanium nitride in ethanol, stirring and adding KH560 and deionized water at a speed of 120-150 r / min and a temperature of 40-50° C., and reacting for 3-5 hours to obtain pretreated titanium nitride; mixing the pretreated lanthanum hexaboride, the pretreated titanium nitride, N,N-dimethylcyclohexylamine and DMF, and reacting for 6-8 hours at a speed of 120-150 r / min and a temperature of 20-25° C. to obtain a composite filler;
[0010] Step A2: octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 105-110° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, acrylic acid, chloroplatinic acid and DMF are uniformly mixed, and the reaction is carried out for 3-5 hours at a speed of 150-200 r / min and a temperature of 60-70° C. to obtain modified polysiloxane;
[0011] Step A3: The modified polysiloxane, allyl alcohol, potassium carbonate and DMF are mixed evenly, and the reaction is carried out for 10-15 hours at a speed of 200-300r / min and a temperature of 70-75°C, and the pH value is adjusted to be acidic to obtain a modified monomer. The terephthalic acid, ethylene glycol, modified monomer, composite filler and antimony acetate are mixed evenly, and the reaction is carried out for 3-5 hours at a speed of 60-80r / min, a temperature of 210-220°C and a pressure of 0.3-0.5MPa. The temperature is raised to 260-265°C, and the pressure is reduced to 50-60Pa. The reaction is carried out for 1-1.5 hours, and the material is discharged and pressed to obtain a base film.
[0012] Furthermore, the amount of KH550 used in step A1 is 3% of the mass of lanthanum hexaboride, the amount of KH560 used is 3% of the mass of titanium nitride, the mass ratio of pretreated lanthanum hexaboride and pretreated titanium nitride is 1:1, and the amount of N,N-dimethylcyclohexylamine used is 2% of the mass of pretreated lanthanum hexaboride.
[0013] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step A2 is 1.4:1:3:2, the molar ratio of dihydrogenpolysiloxane and acrylic acid is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of acrylic acid.
[0014] Furthermore, the molar ratio of the chloropropyl group, allyl alcohol and potassium carbonate on the modified polysiloxane described in step A3 is 1:1:2, the dosage ratio of terephthalic acid, ethylene glycol, modified monomer and composite filler is 60mmo l:120mmo l:20mmo l:1g, and the dosage of antimony acetate is 1% of the total mass of terephthalic acid, ethylene glycol and modified monomer.
[0015] Further, the modified coating is prepared by the following steps:
[0016] Step B1: 1,4-phenylenediboronic acid, 1-thioglycerol and tetrahydrofuran are mixed evenly, and reacted for 20-25 hours at a speed of 150-200 r / min and a temperature of 25-30° C. to obtain intermediate 1; intermediate 1, castor oil, benzoin dimethyl ether and DMF are mixed evenly, nitrogen is introduced for protection, and reacted for 3-5 hours at a speed of 120-150 r / min and 365 nm ultraviolet light irradiation to obtain a modifier;
[0017] Step B2: Polyethylene glycol and isophorone diisocyanate are mixed evenly, stirred and a modifier is added at a rotation speed of 120-150 r / min and a temperature of 20-25° C., and the mixture is reacted for 30-40 minutes, and then hydroxyethyl acrylate is added, and the reaction is continued for 30-40 minutes to obtain polyurethane acrylate. The following raw materials are weighed in parts by weight: 60-80 parts of polyurethane acrylate, 30-40 parts of N,N'-bis(acryloyl)cystamine, 30-50 parts of ethanol, 30-50 parts of acetone and 3-5 parts of 1-hydroxycyclohexyl phenyl ketone, and the raw materials are mixed evenly to obtain a modified coating.
[0018] Furthermore, the molar ratio of 1,4-phenylenediboronic acid and 1-thioglycerol in step B1 is 1:2, the molar ratio of intermediate 1 and castor oil is n:n+1, n is a natural number greater than 0, and the amount of benzoin dimethyl ether is 5‰ of the mass of intermediate 1.
[0019] Furthermore, the mass ratio of the polyethylene glycol, isophorone diisocyanate, modifier and hydroxyethyl acrylate described in step B2 is 12:28:35:2, and the molecular weight of the polyethylene glycol is 2000.
[0020] Beneficial effects of the present invention: The automotive thermal insulation film disclosed by the present invention uses a substrate as a sputtering substrate, zinc aluminum oxide as a first target material, tin antimony oxide as a second target material, and zinc aluminum oxide as a third target material, and is sputtered in sequence to form a sputtering layer to obtain a modified substrate, and a modified coating is coated on a side of the modified substrate away from the sputtering layer, and ultraviolet curing is performed to obtain an automotive thermal insulation film, and the substrate is treated with KH550 using lanthanum hexaboride as a raw material, so that amino groups are grafted on the surface of lanthanum hexaboride to obtain pretreated lanthanum hexaboride, and nitride is Titanium is treated with KH560 so that epoxy groups are grafted onto the surface of titanium nitride to obtain pretreated titanium nitride. Pretreated lanthanum hexaboride and pretreated titanium nitride are reacted so that amino groups on the surface of pretreated lanthanum hexaboride react with epoxy groups on the pretreated titanium nitride to form hydroxyl groups to obtain a composite filler. Octamethylcyclotetrasiloxane and γ-chloropropylheptamethylcyclotetrasiloxane are ring-opened and polymerized with tetramethyldisiloxane to form dihydrogenpolysiloxane. Dihydrogenpolysiloxane and acrylic acid are reacted with SiH bonds on dihydrogenpolysiloxane and double bonds on acrylic acid under the action of chloroplatinic acid to obtain modified polysiloxane. Modified polysiloxane and allyl alcohol are reacted with chlorine atoms on the side chains of modified polysiloxane and hydroxyl groups on allyl alcohol under the action of potassium carbonate, and the pH value is adjusted to be acidic to obtain a modified monomer. Terephthalic acid, ethylene glycol, the modified monomer and the composite filler are evenly mixed, esterified and polymerized, and the material is discharged and pressed to obtain a base film.
[0021] The modified coating is prepared by reacting 1,4-phenylenediboronic acid with 1-thioglycerol, so that the boric acid group on the 1,4-phenylenediboronic acid reacts with the hydroxyl group on the 1-thioglycerol to form a borate ester, and preparing an intermediate 1. The intermediate 1 and castor oil are reacted under the action of benzoin dimethyl ether, so that the thiol group on the intermediate 1 reacts with the double bond on the castor oil to prepare a modifier. Polyethylene glycol and isophorone diisocyanate are reacted to form a polyurethane prepolymer, which is chain extended with the modifier and finally terminated with hydroxyethyl acrylate to prepare polyurethane acrylate. The polyurethane acrylate, N,N'-bis(acryloyl)cystamine, acetone and 1-hydroxycyclohexylphenyl ketone are uniformly mixed to prepare the modified coating.
[0022] When the modified coating is applied to the side of the modified substrate away from the sputtering layer and irradiated with ultraviolet light, the double bonds on the surface of the modified substrate and the double bond-containing substances in the modified coating are polymerized under the action of 1-hydroxycyclohexyl phenyl ketone, thereby increasing the adhesion effect of the modified coating to the substrate. The polyurethane acrylate in the modified coating has a branched structure, and the middle position and the end of the molecular chain segment contain unsaturated double bonds, which makes the modified coating have good scratch resistance after curing. At the same time, it contains disulfide bonds and borate structures, and can self-repair in a short time after scratches appear on the thermal insulation film. The cooperation of multiple sputtering layers and base films can reflect heat well, thereby improving the thermal insulation effect of the thermal insulation film. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Embodiment 1: A method for preparing an automobile thermal insulation film, comprising the following steps:
[0025] The substrate was used as a sputtering substrate, zinc aluminum oxide was used as the first target, antimony tin oxide was used as the second target, and zinc aluminum oxide was used as the third target. Under the conditions of a sputtering power of 80 W, an argon flow rate of 25 sccm, and a sputtering gas pressure of 0.75 Pa, sputtering treatment was performed in sequence to form a sputtering layer to obtain a modified substrate. A modified coating was coated on the side of the modified substrate away from the sputtering layer. Under the conditions of a temperature of 30°C and irradiation with 365 nm ultraviolet light, UV curing was performed for 10 minutes to obtain an automotive thermal insulation film.
[0026] The mass ratio of zinc oxide to aluminum oxide in the first target material zinc oxide aluminum is 98:2, and the background vacuum degree is 6×10 -4 The mass ratio of tin oxide to antimony oxide in the second target material tin antimony oxide is 95:5, and the background vacuum is 5×10 -4 , the third target material is the same as the first target material.
[0027] The base film is made by the following steps:
[0028] Step A1: Disperse lanthanum hexaboride in ethanol, stir and add KH550 and deionized water at a speed of 120 r / min and a temperature of 40°C, and react for 3 hours to obtain pretreated lanthanum hexaboride; disperse titanium nitride in ethanol, stir and add KH560 and deionized water at a speed of 120 r / min and a temperature of 40°C, and react for 3 hours to obtain pretreated titanium nitride; mix the pretreated lanthanum hexaboride, pretreated titanium nitride, N,N-dimethylcyclohexylamine and DMF, and react for 6 hours at a speed of 120 r / min and a temperature of 20°C to obtain a composite filler;
[0029] Step A2: octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 3 hours at a speed of 120 r / min and a temperature of 105° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, acrylic acid, chloroplatinic acid and DMF are mixed uniformly, and the mixture is reacted for 3 hours at a speed of 150 r / min and a temperature of 60° C. to obtain modified polysiloxane;
[0030] Step A3: Evenly mix the modified polysiloxane, allyl alcohol, potassium carbonate and DMF, react at a speed of 200 r / min and a temperature of 70°C for 10 hours, adjust the pH value to be acidic, and obtain a modified monomer; evenly mix terephthalic acid, ethylene glycol, modified monomer, composite filler and antimony acetate, react at a speed of 60 r / min, a temperature of 210°C and a pressure of 0.3 MPa for 3 hours, then heat to 260°C, reduce the pressure to 50 Pa, react for 1 hour, discharge the material and press the film to obtain a base film.
[0031] The amount of KH550 used in step A1 is 3% of the mass of lanthanum hexaboride, the amount of KH560 used is 3% of the mass of titanium nitride, the mass ratio of pretreated lanthanum hexaboride to pretreated titanium nitride is 1:1, and the amount of N,N-dimethylcyclohexylamine used is 2% of the mass of pretreated lanthanum hexaboride.
[0032] The molar ratio of octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step A2 is 1.4:1:3:2, the molar ratio of dihydrogenpolysiloxane and acrylic acid is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of acrylic acid.
[0033] The molar ratio of the chloropropyl group, allyl alcohol and potassium carbonate on the modified polysiloxane described in step A3 is 1:1:2, the amount ratio of terephthalic acid, ethylene glycol, modified monomer and composite filler is 60mmol:120mmol:20mmol:1g, and the amount of antimony acetate is 1% of the total mass of terephthalic acid, ethylene glycol and modified monomer.
[0034] The modified coating is prepared by the following steps:
[0035] Step B1: 1,4-phenylenediboronic acid, 1-thioglycerol and tetrahydrofuran were mixed evenly, and the mixture was reacted at a speed of 150 r / min and a temperature of 25° C. for 20 h to obtain intermediate 1; intermediate 1, castor oil, benzoin dimethyl ether and DMF were mixed evenly, nitrogen was introduced for protection, and the mixture was reacted at a speed of 120 r / min and irradiated with 365 nm ultraviolet light for 3 h to obtain a modifier;
[0036] Step B2: Mix polyethylene glycol and isophorone diisocyanate evenly, stir and add a modifier at a speed of 120 r / min and a temperature of 20°C, react for 30 minutes, add hydroxyethyl acrylate, and continue to react for 30 minutes to obtain polyurethane acrylate. Weigh the following raw materials in parts by weight: 60 parts of polyurethane acrylate, 30 parts of N,N'-bis(acryloyl)cystamine, 30 parts of ethanol, 30 parts of acetone and 3 parts of 1-hydroxycyclohexyl phenyl ketone, mix the raw materials evenly, and obtain a modified coating.
[0037] The molar ratio of 1,4-phenylenediboronic acid to 1-thioglycerol in step B1 is 1:2, the molar ratio of intermediate 1 to castor oil is 1:2, and the amount of benzoin dimethyl ether is 5‰ of the mass of intermediate 1.
[0038] The mass ratio of polyethylene glycol, isophorone diisocyanate, modifier and hydroxyethyl acrylate described in step B2 is 12:28:35:2, and the molecular weight of polyethylene glycol is 2000.
[0039] Embodiment 2: A method for preparing an automobile thermal insulation film, comprising the following steps:
[0040] The substrate was used as a sputtering substrate, zinc aluminum oxide was used as the first target, antimony tin oxide was used as the second target, and zinc aluminum oxide was used as the third target. Under the conditions of a sputtering power of 90 W, an argon flow rate of 30 sccm, and a sputtering gas pressure of 0.85 Pa, sputtering treatment was performed in sequence to form a sputtering layer to obtain a modified substrate. A modified coating was coated on the side of the modified substrate away from the sputtering layer. Under the conditions of a temperature of 35°C and irradiation with 365 nm ultraviolet light, UV curing was performed for 15 minutes to obtain an automotive thermal insulation film.
[0041] The mass ratio of zinc oxide to aluminum oxide in the first target material zinc oxide aluminum is 98:2, and the background vacuum degree is 6×10 -4 The mass ratio of tin oxide to antimony oxide in the second target material tin antimony oxide is 95:5, and the background vacuum is 5×10 -4 , the third target material is the same as the first target material.
[0042] The base film is made by the following steps:
[0043] Step A1: Disperse lanthanum hexaboride in ethanol, stir and add KH550 and deionized water at a speed of 150 r / min and a temperature of 45°C, and react for 4 hours to obtain pretreated lanthanum hexaboride; disperse titanium nitride in ethanol, stir and add KH560 and deionized water at a speed of 120 r / min and a temperature of 45°C, and react for 4 hours to obtain pretreated titanium nitride; mix the pretreated lanthanum hexaboride, pretreated titanium nitride, N,N-dimethylcyclohexylamine and DMF, and react for 7 hours at a speed of 120 r / min and a temperature of 25°C to obtain a composite filler;
[0044] Step A2: octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 4 hours at a speed of 120 r / min and a temperature of 110° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, acrylic acid, chloroplatinic acid and DMF are mixed uniformly, and the mixture is reacted for 4 hours at a speed of 200 r / min and a temperature of 65° C. to obtain modified polysiloxane;
[0045] Step A3: Evenly mix the modified polysiloxane, allyl alcohol, potassium carbonate and DMF, react at a speed of 300 r / min and a temperature of 75°C for 10 hours, adjust the pH value to be acidic, and obtain a modified monomer; evenly mix terephthalic acid, ethylene glycol, modified monomer, composite filler and antimony acetate, react at a speed of 60 r / min, a temperature of 215°C and a pressure of 0.4 MPa for 4 hours, then heat to 265°C, reduce the pressure to 55 Pa, react for 1 hour, discharge the material and press the film to obtain a base film.
[0046] The amount of KH550 used in step A1 is 3% of the mass of lanthanum hexaboride, the amount of KH560 used is 3% of the mass of titanium nitride, the mass ratio of pretreated lanthanum hexaboride to pretreated titanium nitride is 1:1, and the amount of N,N-dimethylcyclohexylamine used is 2% of the mass of pretreated lanthanum hexaboride.
[0047] The molar ratio of octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step A2 is 1.4:1:3:2, the molar ratio of dihydrogenpolysiloxane and acrylic acid is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of acrylic acid.
[0048] The molar ratio of the chloropropyl group, allyl alcohol and potassium carbonate on the modified polysiloxane described in step A3 is 1:1:2, the amount ratio of terephthalic acid, ethylene glycol, modified monomer and composite filler is 60mmol:120mmol:20mmol:1g, and the amount of antimony acetate is 1% of the total mass of terephthalic acid, ethylene glycol and modified monomer.
[0049] The modified coating is prepared by the following steps:
[0050] Step B1: 1,4-phenylenediboronic acid, 1-thioglycerol and tetrahydrofuran were mixed evenly, and reacted at a speed of 150 r / min and a temperature of 30° C. for 25 h to obtain intermediate 1; intermediate 1, castor oil, benzoin dimethyl ether and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 120 r / min and 365 nm ultraviolet light irradiation for 4 h to obtain a modifier;
[0051] Step B2: Mix polyethylene glycol and isophorone diisocyanate evenly, stir and add a modifier at a speed of 150 r / min and a temperature of 20°C, react for 35 minutes, add hydroxyethyl acrylate, and continue to react for 35 minutes to obtain polyurethane acrylate. Weigh the following raw materials in parts by weight: 70 parts of polyurethane acrylate, 35 parts of N,N'-bis(acryloyl)cystamine, 40 parts of ethanol, 40 parts of acetone and 4 parts of 1-hydroxycyclohexyl phenyl ketone, mix the raw materials evenly, and obtain a modified coating.
[0052] The molar ratio of 1,4-phenylenediboronic acid to 1-thioglycerol in step B1 is 1:2, the molar ratio of intermediate 1 to castor oil is 2:3, and the amount of benzoin dimethyl ether is 5‰ of the mass of intermediate 1.
[0053] The mass ratio of polyethylene glycol, isophorone diisocyanate, modifier and hydroxyethyl acrylate described in step B2 is 12:28:35:2, and the molecular weight of polyethylene glycol is 2000.
[0054] Embodiment 3: A method for preparing an automobile thermal insulation film, comprising the following steps:
[0055] The substrate was used as a sputtering substrate, zinc aluminum oxide was used as the first target, antimony tin oxide was used as the second target, and zinc aluminum oxide was used as the third target. Under the conditions of a sputtering power of 100 W, an argon flow rate of 40 sccm, and a sputtering gas pressure of 1 Pa, sputtering treatment was performed in sequence to form a sputtering layer to obtain a modified substrate. A modified coating was coated on the side of the modified substrate away from the sputtering layer. Under the conditions of a temperature of 40°C and irradiation of 365 nm ultraviolet light, ultraviolet curing was performed for 15 minutes to obtain an automotive thermal insulation film.
[0056] The mass ratio of zinc oxide to aluminum oxide in the first target material zinc oxide aluminum is 98:2, and the background vacuum degree is 6×10 -4 The mass ratio of tin oxide to antimony oxide in the second target material tin antimony oxide is 95:5, and the background vacuum is 5×10 -4 , the third target material is the same as the first target material.
[0057] The base film is made by the following steps:
[0058] Step A1: Disperse lanthanum hexaboride in ethanol, stir and add KH550 and deionized water at a speed of 150 r / min and a temperature of 50°C, and react for 5 hours to obtain pretreated lanthanum hexaboride; disperse titanium nitride in ethanol, stir and add KH560 and deionized water at a speed of 150 r / min and a temperature of 50°C, and react for 5 hours to obtain pretreated titanium nitride; mix the pretreated lanthanum hexaboride, pretreated titanium nitride, N,N-dimethylcyclohexylamine and DMF, and react for 8 hours at a speed of 150 r / min and a temperature of 25°C to obtain a composite filler;
[0059] Step A2: octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 5 hours at a speed of 150 r / min and a temperature of 110° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, acrylic acid, chloroplatinic acid and DMF are mixed uniformly, and the mixture is reacted for 5 hours at a speed of 200 r / min and a temperature of 70° C. to obtain modified polysiloxane;
[0060] Step A3: Evenly mix the modified polysiloxane, allyl alcohol, potassium carbonate and DMF, react at a speed of 300 r / min and a temperature of 75°C for 15 hours, adjust the pH value to be acidic, and obtain a modified monomer; evenly mix terephthalic acid, ethylene glycol, modified monomer, composite filler and antimony acetate, react at a speed of 80 r / min, a temperature of 220°C and a pressure of 0.5 MPa for 5 hours, then heat to 265°C, reduce the pressure to 60 Pa, react for 1.5 hours, discharge the material and press the film to obtain a base film.
[0061] The amount of KH550 used in step A1 is 3% of the mass of lanthanum hexaboride, the amount of KH560 used is 3% of the mass of titanium nitride, the mass ratio of pretreated lanthanum hexaboride to pretreated titanium nitride is 1:1, and the amount of N,N-dimethylcyclohexylamine used is 2% of the mass of pretreated lanthanum hexaboride.
[0062] The molar ratio of octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step A2 is 1.4:1:3:2, the molar ratio of dihydrogenpolysiloxane and acrylic acid is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of acrylic acid.
[0063] The molar ratio of the chloropropyl group, allyl alcohol and potassium carbonate on the modified polysiloxane described in step A3 is 1:1:2, the amount ratio of terephthalic acid, ethylene glycol, modified monomer and composite filler is 60mmol:120mmol:20mmol:1g, and the amount of antimony acetate is 1% of the total mass of terephthalic acid, ethylene glycol and modified monomer.
[0064] The modified coating is prepared by the following steps:
[0065] Step B1: 1,4-phenylenediboronic acid, 1-thioglycerol and tetrahydrofuran were mixed evenly, and reacted at a speed of 200 r / min and a temperature of 30° C. for 25 h to obtain intermediate 1; intermediate 1, castor oil, benzoin dimethyl ether and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and 365 nm ultraviolet light irradiation for 5 h to obtain a modifier;
[0066] Step B2: Polyethylene glycol and isophorone diisocyanate are mixed evenly, stirred and a modifier is added at a speed of 150 r / min and a temperature of 25°C, and the mixture is reacted for 40 minutes. Hydroxyethyl acrylate is added and the reaction is continued for 40 minutes to obtain polyurethane acrylate. The following raw materials are weighed in parts by weight: 80 parts of polyurethane acrylate, 40 parts of N,N'-bis(acryloyl)cystamine, 50 parts of ethanol, 50 parts of acetone and 5 parts of 1-hydroxycyclohexyl phenyl ketone. The raw materials are mixed evenly to obtain a modified coating.
[0067] The molar ratio of 1,4-phenylenediboronic acid to 1-thioglycerol in step B1 is 1:2, the molar ratio of intermediate 1 to castor oil is 3:4, and the amount of benzoin dimethyl ether is 5‰ of the mass of intermediate 1.
[0068] The mass ratio of polyethylene glycol, isophorone diisocyanate, modifier and hydroxyethyl acrylate described in step B2 is 12:28:35:2, and the molecular weight of polyethylene glycol is 2000.
[0069] Comparative Example 1: Compared with Example 1, this comparative example does not use the third target material, and the remaining steps are the same.
[0070] Comparative Example 2: Compared with Example 1, the surfaces of lanthanum hexaboride and titanium nitride were not treated, and the remaining steps were the same.
[0071] Comparative Example 3: Compared with Example 1, no composite filler was added in this comparative example, and the remaining steps were the same.
[0072] Comparative Example 4: Compared with Example 1, no modified monomer was added to this comparative example, and the remaining steps were the same.
[0073] Comparative Example 5: Compared with Example 1, ethylene glycol is used to replace the modifier, and the other steps are the same.
[0074] Comparative Example 6: Compared with Example 1, this comparative example does not add N,N'-bis(acryloyl)cystamine, and the remaining steps are the same.
[0075] The thermal insulation films prepared in Examples 1-3 and Comparative Examples 1-6 were made into samples of 190mm×160mm×5mm and irradiated with a 150W infrared lamp for 1 min using a Linshang LS301 thermal insulation film temperature test light box. The temperature difference was calculated, and the pencil hardness of the modified coating layer of the thermal insulation film was tested in accordance with GB / T6739-2022. A 1mm scratch was made on the modified coating layer, and the scratches were observed after 6h, 12h, 18h and 24h in an environment with a temperature of 25°C. The test results are shown in Table 1 below.
[0076] Table 1
[0077]
[0078] It can be seen from the above table that the present invention has good heat insulation and anti-scratch effects.
[0079] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing an automobile thermal insulation film, characterized in that: The specific steps include: The substrate is used as a sputtering substrate, zinc aluminum oxide is used as a first target material, antimony tin oxide is used as a second target material, and zinc aluminum oxide is used as a third target material. The substrate is sputtered in sequence to form a sputtering layer to obtain a modified substrate. A modified coating is coated on the side of the modified substrate away from the sputtering layer, and the coating is cured by ultraviolet light to obtain an automotive thermal insulation film.
2. The method for preparing an automobile thermal insulation film according to claim 1, characterized in that: The mass ratio of zinc oxide to aluminum oxide in the first target material zinc oxide aluminum is 98:2, and the background vacuum degree is 6×10 -4 The mass ratio of tin oxide to antimony oxide in the second target material tin antimony oxide is 95:5, and the background vacuum is 5×10 -4 , the third target material is the same as the first target material.
3. The method for preparing a thermal insulation film for an automobile according to claim 1, characterized in that: The base film is made by the following steps: Step A1: dispersing lanthanum hexaboride in ethanol, stirring and adding KH550 and deionized water to react to obtain pretreated lanthanum hexaboride, dispersing titanium nitride in ethanol, stirring and adding KH560 and deionized water to react to obtain pretreated titanium nitride, and mixing the pretreated lanthanum hexaboride, pretreated titanium nitride, N,N-dimethylcyclohexylamine and DMF to react to obtain a composite filler; Step A2: octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, acrylic acid, chloroplatinic acid and DMF are mixed for reaction to obtain modified polysiloxane; Step A3: Mix modified polysiloxane, allyl alcohol, potassium carbonate and DMF to react, adjust the pH value to be acidic, and obtain a modified monomer; mix terephthalic acid, ethylene glycol, the modified monomer, the composite filler and antimony acetate to react, increase the temperature and reduce the pressure, discharge the material and press the film to obtain a base film.
4. The method for preparing a thermal insulation film for an automobile according to claim 3, characterized in that: The amount of KH550 used in step A1 is 3% of the mass of lanthanum hexaboride, the amount of KH560 used is 3% of the mass of titanium nitride, and the mass ratio of pretreated lanthanum hexaboride to pretreated titanium nitride is 1:
1.
5. The method for preparing an automobile thermal insulation film according to claim 3, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, γ-chloropropylheptamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step A2 is 1.4:1:3:2, and the molar ratio of dihydrogenpolysiloxane and acrylic acid is 1:
2.
6. The method for preparing a thermal insulation film for automobile according to claim 3, characterized in that: The molar ratio of the chloropropyl group, allyl alcohol and potassium carbonate on the modified polysiloxane described in step A3 is 1:1:2, and the amount ratio of terephthalic acid, ethylene glycol, modified monomer and composite filler is 60mmol:120mmol:20mmol:1g.
7. The method for preparing a thermal insulation film for an automobile according to claim 1, characterized in that: The modified coating is prepared by the following steps: Step B1: 1,4-phenylenediboronic acid, 1-thioglycerol and tetrahydrofuran are mixed for reaction to obtain intermediate 1, intermediate 1, castor oil, benzoin dimethyl ether and DMF are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out to obtain a modifier; Step B2: Mix polyethylene glycol and isophorone diisocyanate, stir and add a modifier, react, add hydroxyethyl acrylate, continue the reaction, and prepare polyurethane acrylate. Weigh the following raw materials in parts by weight: 60-80 parts of polyurethane acrylate, 30-40 parts of N,N'-bis(acryloyl)cystamine, 30-50 parts of ethanol, 30-50 parts of acetone and 3-5 parts of 1-hydroxycyclohexyl phenyl ketone, mix the raw materials evenly, and prepare a modified coating.
8. The method for preparing a thermal insulation film for automobile according to claim 7, characterized in that: The molar ratio of 1,4-phenylenediboronic acid and 1-thioglycerol in step B1 is 1:2, and the molar ratio of intermediate 1 and castor oil is n:n+1, where n is a natural number greater than 0.
9. The method for preparing a thermal insulation film for automobile according to claim 7, characterized in that: The mass ratio of polyethylene glycol, isophorone diisocyanate, modifier and hydroxyethyl acrylate described in step B2 is 12:28:35:
2.
10. An automotive thermal insulation film, characterized in that: Prepared according to any one of claims 1 to 9.